The level of awareness, knowledge and infringement on copyright at the University of Ibadan, Nigeria (2020)
The encouragement of intellectual creation is one of the basic prerequisites for social, economic and cultural development of any nation. Copyright was instituted to inspire authors towards more creativity by enabling them to harness the full benefit of their works; however there are issues associated with the compliance on copyright rules. There is a dare need to stem the overwhelming tide of copyright infringement activities going on across the globe. This study examines the level of awareness, knowledge and infringement on copyright at the University of Ibadan. Questionnaire instrument was used for data collection. The population used in the study comprises 150 academic and senior staff of University of Ibadan, Nigeria. The study found that there is low level of awareness and knowledge on copyright matters, as many of the respondents were unfamiliar with matters relating to copyright. The study identified a high level of infringement on copyright in University of Ibadan. The study further advocated for intensive sensitization on copyright matters and enforcement of copyright law within University of Ibadan community in order to strengthen copyright protection